2023
DOI: 10.1002/path.6168
|View full text |Cite
|
Sign up to set email alerts
|

Unleashing the potential of AI for pathology: challenges and recommendations

Abstract: Computational pathology is currently witnessing a surge in the development of AI techniques, offering promise for achieving breakthroughs and significantly impacting the practices of pathology and oncology. These AI methods bring with them the potential to revolutionize diagnostic pipelines as well as treatment planning and overall patient care. Numerous peer‐reviewed studies reporting remarkable performance across diverse tasks serve as a testimony to the potential of AI in the field. However, widespread adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 131 publications
0
2
0
Order By: Relevance
“…The road to clinical adoption of computational pathology is paved with a number of challenges, summarised in Table 1. Whilst a more detailed review can be found in the corresponding computational pathology article of this annual review issue by Professor Rajpoot's group [68], we highlight some key areas of concern focused on the pathologists’ perspective.…”
Section: Challenges Of Building Clinical‐grade Computational Patholog...mentioning
confidence: 99%
“…The road to clinical adoption of computational pathology is paved with a number of challenges, summarised in Table 1. Whilst a more detailed review can be found in the corresponding computational pathology article of this annual review issue by Professor Rajpoot's group [68], we highlight some key areas of concern focused on the pathologists’ perspective.…”
Section: Challenges Of Building Clinical‐grade Computational Patholog...mentioning
confidence: 99%
“…They conclude by suggesting developments to improve these techniques for acceptance in the clinical and research settings. The second review in this section is contributed by Nasir Rajpoot and colleagues from the University of Warwick, Histofy Ltd, and The Alan Turing Institute in the UK [5]. This review provides a detailed summary of the latest developments in AI techniques applied for computational pathology, and gives informative insights for identifying specific challenges and problems that require resolution to allow clinical implementation of models, including the need for large, well-curated datasets and uniform standards and regulatory policies.…”
Section: Computational Pathologymentioning
confidence: 99%